(3bGYOI aj GdbQBf hcdGe Gddg JYGdis - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3GdMeO ddg fSJYjfg hfSJZaQg bGYOI ai GdbQBf hcdGe Gddg JYGdi aEf GdCeI EVWQHJ ai gPG EVWQGHkG YXjekG hJaQbhG hGNJdahG HGdXfhf hEdG ghi HYO eVi GdbQhf GdKdGKI deG MOKJ ajge GdLgejI s
(3BNQgG (B:s
(3Cf bhdg JYGdi (B( (3Cde Pdc GdcJGH dGQjH ajg (B) (3gh cdGe Gddg dG cdGe ZjQg hcdGe Gddg gh eG Jcde Hg dG eG Ndbg ai ZjQg hde jJcde Hg gh s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds